PERUBAHAN POLA PENGETAHUAN REMAJA TENTANG HIV-AIDS (Analisis Lanjut Data SDKI 2007 - 2012) - Dwi Martiana Wati (Jurnal Ilmu Kesehatan Masyarakat, 2015)
Adolescent are known as risky population to HIV-AIDS transmission. The incidence of HIVAIDS among adolescent continues to show significant increment. The initial step in reducing the risk of HIV-AIDS transmission among them can be done by having comprehensive understanding on HIV-AIDS-related knowledge. IDHS as one of national survey that alsoaccomodate HIV-AIDS-related knowledge in addition to sociodemographic dimension, is able to provide the information flow of HIV-AIDS among adolescent themselves. This study aims to provide comprehensive information of HIV-AIDS-related knowledge among adolescent. Theset of data used were obtained from IDHS 2007 and IDHS 2012. Both sets of the data were analyzed using chi-square test at 5 percent significance level. Based on this analysis, it is known that the level of HIV-AIDS-related knowledge among adolescent has increased during 2007- 2012. And during this period, they had chosen a more rational sources to obtain adequate information about HIV-AIDS through the involvementof teachers or school,especially for higher-educated ones. In general, the level of HIV-AIDS-related knowledge among adolescent is higher in older male ones, living in urban areas, and highly educated ones. As one of the effort in reducing the risk of HIV-AIDS transmission among adolescent can be done by increasing the involvement of teachers and parents through the provison of adequate and proportionate information about HIV-AIDS. Furthermore, providinginformation regarding HIV-AIDS-related knowledge in adolescent would be much more effective through the implementation of curriculum on HIV-AIDS nationally which is systematically and proportionally arranged in each level of education.Keywords: adolescent, HIV-AIDS, national curriculum